ANALISIS KUALITAS PELAYANAN PUBLIK DI KANTOR DESA REDANG KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Putra, Muhklas Adi; Dewi, Kurnia (JURNAL MANAJEMEN DAN BISNIS, 2018)
The government as a public sector institution carries out and provides public services which are vital for the public interest. This study aims to determine the Quality of Public Services at the Redang Village Office in West Rengat District, Indragiri Hulu Regency. This research used qualitative descriptive analysis, and to collect all the data this research used interviews, observation and documentation. The results of this study indicate that in general the quality of public services in the Redang Village Office in West Rengat District, Indragiri Hulu Regency is seen from five indicators are: Tangibles (real evidence), Reliability, Resposiveness, Assurance, and Empaty (empathy) is still lacking in quality. Likewise, the Redang Village apparatus must further improve the quality of its services by increasing the ability and motivation and discipline.